Punishment of Criminal Act of Accusing Adultery (Qadzaf) in Indonesian Positive Law: Perspective of Maqasid al-Sharia - Sudarti Sudarti; Ainun Najib (Justicia Islamica, 2021)
Amid the hectic new social space (virtual space), mediated reality, and an era of disruption, the truth of information spread via media is hard to determine, especially with the outbreak of hoaxes that have become a trending issue in the past few decades. Hoaxes are a virtual crime, an act committed via the spread of false stories. Hoaxes can be in the form of accusations of another person committing an immoral act and defamation (assassination character), in this case, accusing another person doing adultery. The author argues that the issue of the criminal act of accusing adultery (qadzaf) in positive Indonesian law is significant to be studied since provisions of positive Indonesian law, as stated in the Criminal Code, do not specifically discuss the criminal act of accusing adultery (qadzaf). This study aimed to analyze the problem of the criminal act of accusing adultery (qadzaf) in positive law by using maqasid al-Sharia. The study is library research conducted by examining materials from the main book relating to problems and other supporting qualitative research studies. This research employed a descriptive-analytical method by describing the legal materials obtained, and then they were analyzed using Maqasid al-Sharia. The research results showed that punishment for the perpetrator of a criminal act of accusing adultery (qadzaf) as regulated in Article 310 paragraph (1) of the Criminal Code is a maximum imprisonment of nine months and or a maximum fine of four thousand and five hundred rupiahs. The aspect of darÅ«riyyÄt about punishment for perpetrators of accusing adultery (qadzaf) is the protection of honor (á¸¥ifz al-”˜ird). This aspect relates to everyone’s honor, which must be protected. Through the legislative institution, a country needs to reconstruct the Criminal Code into a better law, such as revising a particular chapter that has not fulfilled a sense of justice in eradicating crime very disturbing since a policy must righteously be able to settle the societal problems. Based on the changes in law, following the development of social life and technology today is inevitable.